Trade and traffic in the North Atlantic [electronic resource] : observations in reference to the proposed steam communication between Liverpool and the North American colonies and Portland, in the United States, by means of the North Atlantic Steam Navigation Company. - North Atlantic Steam Navigation Company. (London : [s.n.], 1857)
'"It is scarcely possible to repress astonishment at the amount of intercourse between this country and the States ." --Times, Jan. 10, 1857.' Electronic reproduction. Mode of access: Internet. 44